PENERAPAN E-GOVERNMENT DALAM MENINGKATKAN PELAYANAN PUBLIK PADA BADAN SISTEM ADMINISTRASI MANUNGGAL SATU ATAP PROVINSI SULAWESI TENGGARA - Muhammad Amir; Nurul Hikma (Journal Publicuho, 2021)
This study aims to determine the application of e-government in improving service quality at the Technical Implementation Unit of the Kendari one-stop Manunggal Administration system Agency, Southeast Sulawesi Province. This type of research is descriptive qualitative. Data collection techniques were carried out by means of library research and field research using interview, documentation, and observation methods. The results of this study the application of e-government is very helpful in the process of paying tax services, in this case, it can make it easier for both the local government and the people who make payments. In addition, the implementation of e-government in improving the quality of services at the Technical Implementation Unit of the Kendari One Roof Manunggal Administration System is also considered quite good, judging from the respondents’ responses to the four indicators, namely tangible, reliability, and responsiveness and courtesy, so it can be said that the organization’s goals have been achieved. Sufficient to achieve its objectives in providing services. Tax payment services at the Technical Implementation Unit of the Kendari One-Stop Manunggal Administration System are still quite good overall. This is because the services provided by the One-Stop Manunggal Administration System are transparent, safe, and easy so that people can feel satisfied with the services they receive.